Analysis of Asean Charter Related To Asean Dispute Settlement Mechnism - Limsiritong, Nattapat (International Journal of Multidisciplinary in Management and Tourism, 2020)
The Association of Southeast Asia (ASEAN) are recognized as the well-known regional organization in South East Asia regional. As normal as other inter organizations, ASEAN also has its own Dispute Settlement Mechanism (DSM) to handle with the disputes among ASEAN Member States. Since the establishment of ASEAN in the cold war era till the heading to ASEAN Community by the end of 2015, there are many treaties related to DSM such as ASEAN Charter (2007), Treaty of Amity and Cooperation in Southeast Asia (1976, 1987, 1998, 2010), ASEAN Protocol on Enhanced Dispute Settlement Mechanism (1996, 2004), Protocol to the ASEAN Charter on Dispute Settlement Mechanisms (2010), and etc. This article will show the reader an overview of ASEAN DSM and how to apply these DSMs through the ASEAN Charter.